From farm to table: How are governments keeping food systems functioning during COVID-19? - Kennedy, Adam; Resnick, Danielle (International Food Policy Research Institute, 2020)
With the initial onset of COVID-19, pictures of empty supermarket shelves and panic buying raised questions about the impacts of the pandemic on food supply chains. Around the world, governments have responded in multiple ways to address some of the major constraints generated by lockdowns, restrictions on transport, and financial stresses experienced by farmers, retailers, and consumers (Hawkes 2020; Reardon and Swinnen 2020). Drawing on the data collected for 28 countries for IFPRI’s COVID-19 Policy Response (CPR) Portal (IFPRI 2020), this brief summarizes the distribution of government policy choices, highlighting where innovations emerged as well as where there has been a reversion to the status quo.